Membangun Jiwa Entrepreneurship - Fathurohmman Fathurohmman, (UIN Siber Syekh Nurjati Cirebon, 2017)
The soul is not a physical part of a person's mind and personality include, synonymous with the spirit, mind, or the crew themselves. The use of the term is more often associated with life compared to the mundane spirit. Personality includes mental and physical attitude. According to Professor Edwood Chapman, mental attitude is a way of communicating or expressing a mood or character to others. If our expression to others positively, then we called the person a positive mental attitude. Conversely, if our expression to others negative, then we called the person a negative mental attitude. While enrteprenuer is one who is able to create a new business as well as creative and innovative to take the risk and uncertainty in order to achieve profit and growth by identifying opportunities and threats as well as combining with its available resources.Entrepreneurship is the human soul owner who has a bit of foresight. He will always coexist interdependent with each other. Interdependent souls will bring glory to the appropriate disposition of individuals, human dignity has created for mutual interdependence, and able to take advantage of any of anything in the world.Key Word: Build, enrteprenuer.